CRIMINAL SANCTIONS OF LIWATH AND MUSAHAQAH CONTROLLERS IN POSITIVE LAW AND JINAYAH FIQH - Sumardi Efendi (Program Pascasarjana IAIN Langsa, 2020)
Liwath and musahaqah are sexual deviations committed by people who have sex disorders in general. This deviant sex disorder was first practiced by the Prophet Lut, and this behavior was directly punished by the perpetrator by Allah SWT. because this behavior is considered to violate the nature that Allah SWT has given to humans. The aim is to find out the difference in sanctions for liwath and musahaqah actors in positive law and jinayah fiqh. This type of research in scientific writing is a type of library research that is based on library deeds or documentation that has been done previously to support research. From the research results, it is concluded that positive law and jinayah fiqh both provide legal rewards for homosexual and lesbian perpetrators and the difference between positive law and jinayah fiqh is regarding the severity and lightness of the punishments given to liwath and musahaqah perpetrators.